Manajemen Berbasis Sekolah dalam Menyelesaikan Bullying di Mis Jayasari Langkaplancar - Arlan Hidayatulloh; Yayat Hidayat; Irpan Ilmi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The purpose of this study is to analyze the extent to which school-based management is applied in handling bullying cases at MIS Jayasari Langkaplancar. The method applied in this research is descriptive qualitative. Data collection techniques were carried out by observation, documentation and interviews with the principal, teachers and students of MIS Jayasari Langkaplancar.in addition, the reseracher also conducted a literature study on a number of scientific journals and books related to the topic to be studied. The results showed that school-based management proved efefctive in reducing bullying incidents at MIS Jayasari Langkaplancar. The results showed that school-based management proved effective in reducing bullying incidents at MIS Jayasari Langkaplancar. The indicators of school-based manajement in resolving bullying applied at MIS Jayasari Langkaplancar are school indepedence, principal leadership, active participation of all stakeholders (teachers, students,parents, and community), school transparency, school accountability, school sustainability, and the effectiveness and efficiency of school-based manajement.